The potential role of mobile network in disseminating flood warning: a study on a pilot project in two upazilas under Manikganj and Tangail - Kamran, M. (BRAC University, 2011)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Master in Disaster Management, 2009.